Pengaruh Tax Planning, Keputusan Investasi Dan Ukuran Perusahaan Terhadap Manajemen Laba (Subsektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019) - Atika Purnamasari (Universitas Islam Bandung, 2021)
This study aims to examine the effect of tax planning, investment decisions and firm size on earnings management in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. Tax Planning is proxied by (Tax Retention Rate) TRR, Investment Decision is proxied by (Total Asset Growth) TAG, Company Size is proxied by Size, and Earnings Management is proxied by Discreationary Accural (DA). The research method used is hypothesis or causal testing. This study uses quantitative secondary data in the form of financial statements for the 2015-2019 period from Food and Beverage Subsector Companies listed on the Indonesia Stock Exchange, which were taken as samples of 12 companies. The statistical analysis used in this study is multiple regression analysis, while the hypothesis testing used is the t test, r test, and the determinant coefficient (R2). The results of the research test show that (1) Tax Planning has an effect on Earnings Management, (2) Investment Decisions have no effect on Earnings Management, (3) Company Size has an effect on Earnings Management, (4) Simultaneously Tax Planning, Investment Decisions and Company Size have an effect to Earnings Management.